Transient Stability of Epigenetic Population Differentiation in a Clonal Invader - Shi, Wen; Chen, Xiaojie; Gao, Lexuan; Xu, Cheng-Yuan; Ou, Xiaokun; Bossdorf, Oliver; Yang, Ji; Geng, Yupeng (Frontiers in Plant Science, 2019)
Epigenetic variation may play an important role in plants coping with new and heterogeneous environments. Although significant epigenetic differentiation among contrasting habitats has been frequently observed in field, its stability remains largely unknown. Here, we used field monitoring, multi-generation cultivation in common garden, and growth chamber to investigate the dynamics of epigenetic variation in Alternanthera philoxeroides, a clonal invasive weed in China. Using AFLP and MS-AFLP markers, we found little genetic variation, but considerable epigenetic variation, in natural populations along a broad climatic gradient. Repeated measurements indicated that the epigenetic diversity and differentiation was largely stable in field, but showed transient stability and progressive erosion under common environments. It seemed that the epigenetic variations observed in field origin from repeated induction and were reinforced by environments, rather than from spontaneous epimutations selected by environments. Given its limited genetic variation in DNA sequences, this clonal invader may benefit much from epigenetic variations in acclimation to heterogeneous environments across broad climatic gradient.